Intelligence and security informatics Pacific Asia workshop, PAISI 2011, Beijing, China, July 9, 2011, proceedings - Chau, Michael; Wang, Alan G.; Zheng, Xiaolong; Chen, Hsinchun; Zeng, Daniel; Mao, Wenji (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2011, held in Beijing, China, in July 2011. The 8 revised full papers and the 5 short papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on terrorism informatics and crime analysis; intelligence analysis and knowledge discovery; information access and security; and infectious disease informatics.